Exploring the Influence of a principal’s internalized moral perspective towards teacher commitment in Malaysian secondary schools - Kasa, Muhamad Dzahir; Shamsuddin, Muhamad Fahmi; Mohd Yaakob, Mohd Faiz; Yusof, Mat Rahimi; Mohd Sofian, Fatimah Noor Rashidah (Asian Online Journal Publishing Group, 2020)
Authentic leadership principals are an alternative to leadership styles within an organisation intended to create more effective administration in maintaining the trust of subordinates, meeting job expectations, and being able to implement change despite facing challenges. However, authentic leadership capabilities of school-style leadership adaptations are still relatively new and unfamiliar. This study aimed to identify the authentic leadership practices applied by school principals and their relationship to the commitment of national secondary school teachers in the district of Pendang in a northern state of Peninsular Malaysia. The research method used was a quantitative survey using a standardised questionnaire. The study respondents consisted of 254 teachers randomly selected from ten national secondary schools under the leadership of principals. The instrument used was adapted from the Authentic Leadership Questionnaire (ALQ -version 1) to measure the dimensions of authentic leadership. Furthermore, the questionaire of organizational commitment was used to measure the level of teachers’ commitment to the organisation. Data processing was performed using SEM-PLS 3.0. Results showed that the internalised moral perspective dimension of authentic leadership significantly influenced teacher commitment. The leaders with these attributes should combine their principles and behaviours in keeping with internal moral standards. This approach should affect the attitudes of teachers and create a changing environment.